PERAN ORGANIZATIONAL CULTURE DALAM PENGARUH TEACHER COMPETENCY DAN WORK ETHICS TERHADAP TEACHER PERFORMANCE DI SEKOLAH MENENGAH ATAS DI KOTA BATAM - Ririn Indahyany; Agustinus Setyawan; Muhammad Donal Mon (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the mediating effect of organizational culture in influencing the direct relationship between teacher competence and work ethic on teacher performance in high schools in Batam City. Data were collected from 368 teacher respondents working in high schools in Batam City using a Likert’s scale questionnaire. A quantitative Method was used with a non – probability sampling technique, and data processing was performed using SEM-PLS analysis. The result showed that Teacher Competency and Work Ethics have a positive and significant influence on Organizational Culture in high schools in Batam City. However, Organizational Culture and Teacher Competency have no positive and insignificant influence on Teacher Performance in High Schools in Batam City. These findings indicate that teacher performance improvement is not solely determined by competency and organizational culture, but is influence by factors beyond the research model. Organizational culture was unable to mediate the relationship between work ethics and teacher performance